Chinese herbal medicine for small cell lung cancer patients: A protocol for a systematic review and meta-analysis. Issue 52 (24th December 2020) - Mi, Xue; Zhang, Xiwen; He, Shulin; Zhang, Zhenhua; Qi, Runzhi; Jiang, Juling; Chen, Shuntai; Zheng, Honggang; Hua, Baojin
Abstract: Background: Small cell lung cancer (SCLC) is an aggressive disease. Chemotherapy is the standard treatment for SCLC, but the resistance and the adverse effects of Chemotherapy still remains a major problem. Although Chinese herbal medicine (traditional Chinese medicine) is wildly applied for patients with SCLC in China, the evidence of traditional Chinese medicine in the treatment for SCLC is limited. Method: We conducted a systematic search of PubMed, EMBASE, the Chinese National Knowledge Infrastructure, the VIP Information Database, and the Wanfang Database for relevant studies. Only randomized controlled trials were included. Two investigators independently reviewed the included studies and extracted relevant data. The effect estimate of interest was the relative risk or mean difference with 95% confidence intervals. Ethics and dissemination: Ethical approval is not required, as this study is based on the review of published research. This review will be published in a peer-reviewed journal and disseminated both electronically and in print. INPLASY registration number: INPLASY2020110055